Assessment of COVID-19 prevention practice and associated factors in Jimma town, Ethiopia: A mixed study - Deriba Bedane; Daba Abdissa; Bati Leta; Urge Gerema; Abraham Lomboro; Guta Kune; Abiru Neme; Kumsa Kene; Nimona Berhanu; Abebe Dukessa Dubiwak; Kasahun Girma Tareke (Frontiers Media S.A., 2022)
BackgroundCOVID-19 has affected the mental and physical wellbeing, social structure, countries' economy as well as individuals and community resilience, trust, and inequalities among societies. However, now almost all of the activities have been returned to the pre-corona era, despite the emergence of new strains and the spread of the disease. Hence, this study was conducted to assess COVID-19 prevention practice and the associated factors.Materials and methodsA community-based cross-sectional study triangulated with the qualitative findings was conducted in Jimma town, Oromia, Ethiopia. A total of 422 sample households were involved in the quantitative study. The quantitative data were collected using a structured questionnaire and 12 key informants were also interviewed for the qualitative part. The quantitative data were processed and entered into the Epi Data version 4.6 (software) and analyzed using SPSS 26.0. Similarly, the qualitative data were analyzed using ATLASti.7.1.04 software package. Descriptive statistics and binary logistics regression (p < 0.25) were conducted to identify the candidate variable for multivariable logistics regression analysis (p < 0.05) and a 95% confidence interval was used to establish the level of significance of the variables with the practice.ResultsInterviews were conducted with a total of 422 participants, yielding a response rate of 100%. Good preventive practices were found to be adopted by 13.3% of the respondents. People aged ≥ 50 years, [AOR = 2.85, 95%, CI = 1.246-0.53] who recovered from COVID-19, [AOR = 2.41, 95%, CI = 1.184-0.92], had chronic diseases [AOR = 3.70, 95%, CI = 1.887-0.25], and living with COVID-19 high risk [AOR = 2.96, 95%, CI = 1.475-0.991 were independently associated with good preventive practices.ConclusionIn this study, it was understood that there were poor COVID-19 preventive practices among the study participants. There was a disparity in adherence to the preventive practices in relation to (i.e., 50 and above years) the experience of contracting COVID-19 and people aged above 65 years old living with the high-risk group. In addition, the community had different misconceptions or risk perceptions related to COVID-19 infection and preventive practices. This highlights the need to design health education programs and implement risk and/or social and behavior change communication interventions to change perceptions or misconceptions of people or community members to bring about the desired behavioral change and prevent the spread of COVID-19.